The Role of Transformational Leadership and Intrinsic Motivation on Job Competence and its Implications for Job Satisfaction: A Case Study of Public High School Teachers in Cirebon City - Nanik Oktafia; Delia Prayani; Edy Hartono (Indonesian Journal of Advanced Research, 2024)
This study aims to determine the role of transformational leadership and intrinsic Motivation on job satisfaction. In addition, it also aims to see job competence as a mediation between these relationships. This research was conducted in senior high schools, where questionnaires were filled out with saturated sampling. Saturated sampling is a sampling technique in which all members of the population are used as samples. So, the sample in this study amounted to 148 respondents, namely public high school teachers in the city of Cirebon. This research was conducted using quantitative methods, a research method based on the philosophy of positivism, used to research certain populations or samples, data collection using research instruments, and data analysis, which is quantitative or statistical, with the aim of testing predetermined hypotheses. This data was tested using the Structural Equation Model (SEM-PLS). The results of the study found that transformational leadership on job competence has a significant effect, intrinsic Motivation has a significant effect on job competence, transformational leadership is significantly influenced by job satisfaction, intrinsic Motivation and performance satisfaction have a significant effect, while job competence can hurt job satisfaction, between transformational leadership and job satisfaction is direct. Job competence does not play a role in this relationship, which shows rejection; job competence mediates intrinsic Motivation, and job satisfaction does not play a role in this relationship, which shows rejection.